2011
DOI: 10.1103/physrevb.83.184117
|View full text |Cite
|
Sign up to set email alerts
|

Structure and sources of disorder in poly(3-hexylthiophene) crystals investigated by density functional calculations with van der Waals interactions

Abstract: The crystal structure of poly(3-hexylthiophene) (P3HT) has been studied by first-principles calculations based on density functional theory. The generalized gradient approximation is employed and van der Waals interactions are treated accurately by the recently proposed local atomic potential approach. A variety of different models were tested, and the model having the lowest energy is a non-interdigitated structure having an orthorhombic cell with a = 17.2 Å, b = 7.7 Å, and c = 7.8 Å, where a, b, and c are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Larger torsional disorder in RP33 aggregates is a consequence of reduced dispersion interaction enforcing planarization between thiophene units. In the ground state, interchain interactions in aggregated domains consist of π–π interaction between conjugated thiophene units and van der Waals interaction between alkyl chains . Through a temperature-dependent phase change of polyfluorene in the solution phase, Bright et al suggested that the energy required to planarize the polymer backbone is 15.6 kJ/mol .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Larger torsional disorder in RP33 aggregates is a consequence of reduced dispersion interaction enforcing planarization between thiophene units. In the ground state, interchain interactions in aggregated domains consist of π–π interaction between conjugated thiophene units and van der Waals interaction between alkyl chains . Through a temperature-dependent phase change of polyfluorene in the solution phase, Bright et al suggested that the energy required to planarize the polymer backbone is 15.6 kJ/mol .…”
mentioning
confidence: 99%
“…In the ground state, interchain interactions in aggregated domains consist of π−π interaction between conjugated thiophene units and van der Waals interaction between alkyl chains. 32 Through a temperature-dependent phase change of polyfluorene in the solution phase, Bright et al suggested that the energy required to planarize the polymer backbone is 15.6 kJ/mol. 33 This energetic barrier, given by interdigitation of alkyl chains, is surmounted by an energy barrier given by the π−π interaction energy, which is ca.…”
mentioning
confidence: 99%
“…Interactions between the alkyl side chains originating from neighboring lamellae can give rise to ordered stacking in the third dimension, thereby forming P3HT crystals. Indeed, P3HT polymer chains with predominantly head-to-tail ordering (RR) can be orderly stacked along the planes via self-assembly of the noninterdigitated lamellae and enhance π–π stacking, leading to improved carrier mobility across the layer …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, P3HT polymer chains with predominantly head-to-tail ordering (RR) can be orderly stacked along the planes via self-assembly of the noninterdigitated lamellae and enhance π−π stacking, leading to improved carrier mobility across the layer. 89 However, lower-MW polymers with preferential stacking along the (100) plane have more alkyl side chains in-plane, which lead to more stacking via van der Waals interaction and more out-of-plane access to thiophene rings without any steric hindrance. This crystalline configuration of lower-MW polymers might be the main reason for their lower performance and stability compared to high-MW P3HT layers.…”
Section: T H I S C O N T E N T I S O N L Y L I C E N S E D F O R C O ...mentioning
confidence: 99%
“…Predicting P3HT self-assembly in particular, and OPV assemblies in general, is difficult because of the multiple length-scales that matter: atomic orbitals, molecular packing, alignment of crystallites, and thermodynamic phase separation all impact OPV device performance. First principles calculations have the highest resolution and can provide insight into charge transport relationships in P3HT [15,16,17], but their computational demands preclude simulating thousands of atoms—far too small to gain insight into the bulk morphological features that arise from thermodynamic self-assembly. Macroscopic models are successful in predicting device-scale morphologies with thickness ∼100 nm both on-lattice [18,19,20,21,22] and off-lattice [23,24,25], but cannot represent important structural features such as crystallite grain orientations and energetic differences between molecules.…”
Section: Introductionmentioning
confidence: 99%